2020
DOI: 10.3390/app10144987
|View full text |Cite
|
Sign up to set email alerts
|

Release of Antioxidant Compounds of Zingiber officinale by Ultrasound-Assisted Aqueous Extraction and Evaluation of Their In Vitro Bioaccessibility

Abstract: Ginger rhizome is widely used in culinary preparations and in traditional medicine. Its benefits are associated with its antioxidant properties related to phenolics and terpenoids compounds, which use to be thermolabile. Ultrasound-assisted extraction has been useful for enhancing the release of thermosensitive compounds present in vegetable tissues. Therefore, the aim of this study was to evaluate the influence of ultrasound-assisted extraction on the release of antioxidants from ginger in aqueous media as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Contrary to past research, lemon did not produce high antioxidant activity or a high phenolic compound content. For antioxidant assays that are predicated on the antioxidants donating hydrogen to reduce the free radical, the amount of phenolic antioxidants will be correlated with the amount of antioxidant activity, thus, the lower the phenolic content, the more likely it is that the antioxidant capacity of that sample will be lower [52]. Since mint displayed the highest antioxidant activity for most assays, the antioxidant activity in GLMT may be contributed predominantly by mint's polyphenols or other phytochemicals.…”
Section: Phenolic Compound Estimation (Tfc Tpc and Ttc)mentioning
confidence: 99%
“…Contrary to past research, lemon did not produce high antioxidant activity or a high phenolic compound content. For antioxidant assays that are predicated on the antioxidants donating hydrogen to reduce the free radical, the amount of phenolic antioxidants will be correlated with the amount of antioxidant activity, thus, the lower the phenolic content, the more likely it is that the antioxidant capacity of that sample will be lower [52]. Since mint displayed the highest antioxidant activity for most assays, the antioxidant activity in GLMT may be contributed predominantly by mint's polyphenols or other phytochemicals.…”
Section: Phenolic Compound Estimation (Tfc Tpc and Ttc)mentioning
confidence: 99%
“…The values of antioxidant capacity and total phenolics obtained for D. bicolor through a French press (434–2128 mg ET/100 g and 110–1920 mgEFe 2+ /100 g, 684–9929 mg EGA/100 g) are superior to those reported about the extraction of bioactive compounds from several vegetal matrixes including flowers [ 22 ], tea [ 36 ], medicinal and aromatic plants [ 23 , 27 , 30 , 38 ], and agri-food by-products [ 25 , 41 ]. Those studies include the use of different extraction methods (i.e., conventional, microwave, and ultrasound) and involve several extractant agents such as water, methanol, ethanol, acetone, ethyl acetate as well as their mixtures with water.…”
Section: Resultsmentioning
confidence: 64%
“…This is in agreement with data reported for antioxidants extracted from different vegetable matrixes [ 34 , 35 , 36 , 37 ]. Similarly, Contreras-López et al [ 38 ] used thermo-ultrasound, applying temperatures from 30 to near 60 °C to obtain the higher liberation of antioxidant and phenolic compounds from ginger ( Zingiber officinalis ). In our research, it was also observed that the best results were obtained by using times of extraction no longer than 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…Shan et al [63] have reported that a methanolic extract of dried ginger, did not possess a very high phenol content as compared to other spices (6.3 mg GAE/1 g of dry ginger). In a recent report by Contreras-López et al [38], which involved the ultrasound-assisted extraction of whole ginger rhizomes using water as solvent, the authors found low TPC values (ranging from 0.08 to 0.17 mg GAE/g of dry material) due to the effect of the ultrasonic energy which could promote side-reactions between the extracted phenolic compounds, which does not allow their efficient extraction in water.…”
Section: Total Phenolic Content Of the Ginger Extractsmentioning
confidence: 99%
“…To evaluate the use of ginger as a natural source of bioactive compounds, several studies have reported the various extraction methods using common VOCs, in various temperatures and extraction times [1,3,38,39]. However, to our knowledge, there is only one study by Hsieh et al [19] investigating the application of greener techniques such as UAE (using an ultrasonic bath) in combination with NaDESs as extraction media for the extraction of valuable compounds from dry ginger as well as for the optimization of the proposed method.…”
Section: Introductionmentioning
confidence: 99%